ФЛОРИСТИЧЕСКИЙ АНАЛИЗ СЕМЕЙСТВА POLYGONACEAE JUSS. ВО ФЛОРЕ ГОРОДА ФЕРГАНЫ (Multidisciplinary Journal of Science and Technology, 2025)
The article presents an extended floristic and ecological analysis of the Polygonaceae Juss. family within the flora of Fergana city (Uzbekistan). Field and herbarium studies identified 22 species belonging to five genera: Rumex L., Polygonum L., Persicaria Mill., Atraphaxis L., and Fallopia Adans. The genus Rumex L. dominates (45.45 %) and demonstrates a high level of ecological plasticity and adaptability to anthropogenic environments. Life-form analysis shows the prevalence of annual herbs (50 %), while ecological groups are dominated by mesophytes (41 %). The results reveal the structural and ecological composition of the urban flora of Fergana and can serve as a basis for floristic monitoring and comparative ecological studies of urbanized ecosystems.